ENGLISH CONSONANTS AND THEIR BENGALI EQUIVALENTS: A CONTRASTIVE ANALYSIS - Jakir, Jakir (Universitas Islam Sumatera Utara (UISU), 2024)
The paper aimed to investigate the phonetic and phonological differences between the consonant sounds of English and Bengali. Data were collected from secondary and primary sources. Initially, data on the phonetic and phonological properties of English and Bengali consonant sounds were gathered through content analysis of various books and journal articles. These data were then analyzed using contrastive analysis (CA) with theoretical frameworks from Received Pronunciation (RP) and Standard Bengali Pronunciation (SBP). Additionally, two interviews were conducted with English Language Teaching (ELT) experts in Bangladesh, selected through purposive sampling. The experts provided insights into the pronunciation challenges faced by Bangladeshi EFL learners due to differences between English and Bengali consonant sounds, and suggested measures to address these issues. The analysis revealed significant differences between English and Bengali consonant sounds in terms of place and manner of articulation, which contribute to substantial pronunciation problems for Bangladeshi EFL learners. Based on these findings, the study offers recommendations for teaching and learning English consonant pronunciation to EFL learners in Bangladesh.